Réponses

Meilleure réponse !
2013-12-08T00:50:26+01:00
A=4(8x+9)^2=4(64x^2+144x+81)=256x^2+576x+324

B=(5-x)(5-6x)^2=(5-x)(25-60x+36x^2)=125-300x+180x^2-25x+60x^2-36x^3=-36x^3+240x^2-325x+125

C=(7x-4)(7x+4)-(7x-4)=49x^2-16-7x+4=49x^2-7x-12

D=(x+1)^2+(2x+6)(2x-6)=x^2+2x+1+4x^2-36=5x^2+2x-35

E=(x-2)(x+2)-3(4x-2)^2+5(3x+2)(1-7x)=x^2-4-3(16x^2-16x+4)+5(3x-21x^2+2-14x)=x^2-4-48x^2+48x-12+15x-105x^2+10-70x=-152x^2-7x-6

1) x appartient à l'arête du cube donc il ne peut pas être supérieur à 8 et x est une longueur donc il est positif.

2) V(x)=AN*AM*AP=x*x*(8-x)=x^2(8-x)=8x^2-x^3

3) pour x=2 ---> V(x)=-2^3+8*2^2=-8+8*4=-8+32=24 cm^3